Sanitation and the Presence of Cockroaches on Ships at the Port of Yos Sudarso, Ambon - Sofiyan Sofiyan; Henry Setiawan Susanto; Ruddy La Unga (Humanistic Network for Science and Technology (HNST), 2023)
Transmission of the disease via the cockroach vector as a disease transmitter, including those transported via transportation ships arriving from outside Indonesia and vice versa as well as between ports in Indonesia Cockroaches are allowed to transmit diseases, and the Port Health Office (KKP), which is the Technical Implementation Unit (UPT) and head of the Indonesian Ministry of Health, is allowed to prevent and manage this. 112 of the 2,106 ships entering Yos Sudarso port in 2021 were still found to be carrying cockroaches, which can pose risk factors for the spread of illness, according to data collected by the Ambon KKP during surveillance of the ships landing there. This study, which was conducted in July and August 2022 on ships at Yos Sudarso Port, Ambon, was an analytical observational study using a cross-sectional study design approach to analyze ship sanitation parameters for the cockroaches’ presence. As many as 30 ships were used as samples. There was a correlation between ship sanitation and the number of cockroaches, according to a Chi-square test conducted at Yos Sudarso port in Ambon, which had a p value of 0.008, and the results found that the poor level of ship sanitation can lead to the presence of cockroaches. The existence of cockroaches on board can result in a risk of disease transmission, and control measures must be taken quickly. Keywords: ship sanitation; cockroach; port